Controle de vibrações em máquinas rotativas usando ligas com memória de forma - Alves, Marco Túlio Santana (2015)
This work is dedicated to passive and semi-active vibration control of flexible rotors by using shape memory alloys in the support of the system. A rotor represented by a horizontal shaft comprising a rigid disc supported by two bearings with flexible base at both ends was investigated both through numerical simulation and experimentation. The numerical model used in the simulations was obtained according to the Finite Elements Method (FEM). Due to the high number of degrees of freedom this model was reduced in such a way that only the first three bending modes of the rotor. The strategy used to control the vibrations is based on a suspension with a SMA wire elongation system connected to the most flexible bearing. The Bearing Suspension by Wires, or simply, BSW, acts only along the horizontal direction and is encapsulated by a heating chamber whose purpose is to control the wire temperature. Obtaining experimental natural frequencies of the rotor was a fundamental step to adjust the finite elements model. As the system is nonlinear since the SMA elasticity molulus is dependent of the thermo-mechanical state (temperature and strain), an inverse model for the suspension was used in order to solve the nonlinear problem. The constitutive model that governs the SMA behaviour is a modified Brinson s model which considers only the pseudoelastic effect, thus defining a region of interest due to energy dissipation inherent to the hysteretic loop. The experimental part of the work has been carried out by considering several conditions for the rotor operation, namely: rotor at rest, steady state and transient responses. The results, both numerical and experimental, reveal the potential of using shape memory alloys as a feasible alternative to passive and semi-active control of rotors.